Sensitivity to nuclear data of the design of the IFMIF-DONES beam dump - Lopez, Victor; Ogando, Francisco; Sauvan, Patrick (Frontiers in Physics, 2023)
During the commissioning and start-up phases of IFMIF-DONES, the 40 MeV deuteron beam will be stopped in a conical beam stopper made of copper, giving rise to intense neutron fields. Accurate coupled deuteron-neutron transport simulations are required in order to prevent the potential risks to the workers and equipment involved. However, the experimental data concerning the neutron emission under these circumstances is scarce and limited to a particular range of energies. Different deuteron nuclear data libraries such as JENDL-5 and special files of TENDL-2021 exhibit some discrepancies on the spectrum of the emitted neutrons. The discrepancies are present in the high energy tails, beyond the available experimental data. Calculations of the prompt neutron fields have been performed employing both deuteron data libraries, as well as employing an estimation of the neutron energy-angle distribution derived from experimental data at different irradiation energies. Even though the high energy tails represent a small part of the flux, they have a major impact on the dose rates. The disparity of the results evinces large uncertainties in the IFMIF-DONES beam dump design process. Further experiments are required in order to reduce the uncertainty.